Synthesis and Chracaterization of the Nicotinamide-Acetylsalicylato Complexes of Co(II), Ni(II), Cu(II) and Zn(II) - Köse, Dursun Ali; İçbudak, Hasan; Necefoğlu, Hacali (My University, 2007)
Nicotinamide-acetylsalicylato complexes of Co(II), Ni(II), Cu(II), and Zn(II) were synthesised and their structural properties were investigated by employing elemental analysis, magnetic susceptibilitiy, solid state UV-vis, direct injection probe mass, FTIR and thermoanalytic TG-DTG methods. It was found that ratio of metal:ligand:ligand is 1:2:2 and the decomposition of each complex starts with dehydration and follows by decomposition of the nicotinamide and acetylsalicylato, respectively. The thermal dehydration of the complexes takes place in steps from one to two. The decomposition mechanism and thermal stability of the investigated complexes are interpreted in terms of their structures. The final decomposition products are found to be the respective metal oxides
Keywords: Biyoloji